2023
DOI: 10.1017/s0022149x23000196
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses based on molecular and morphological data reveal a new species ofStrigeaAbildgaard, 1790 (Digenea: Strigeidae) and taxonomic changes in strigeids infecting Neotropical birds of prey

Abstract: Members of the genus Strigea Abildgaard, 1790 are endoparasites of birds distributed worldwide. Adults of an undescribed species of the genus Strigea were collected from the intestines of two hawk species (Rupornis magnirostris and Accipiter coperii). Other species identified as Parastrigea macrobursa that were described in Argentina were also recovered from two hawk species (Buteogallus urubitinga and Buteogallus anthracinus) in three localities along the coasts of Mexico. Specimens of the two species were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The recent use of an integrative approach combining morphology, molecular biology and the study of parasites and their hosts is essential and has made it possible to confirm or place species in synonymy and to understand the taxonomy within several genera of this family (Blasco-Costa et al 2016 ; Achatz et al 2020 ; Locke et al 2021 ; Pyrka et al 2021 ; Sokolov et al 2021 ). Regarding the genus Strigea , López-Jiménez et al ( 2023 ) analysed the South American species based on different nuclear and mitochondrial domains. Heneberg et al ( 2018 ) showed the separation of the European species into three clades ( Strigea sensu stricto, Amphistoma and Cryptostrigea ), proved the well-defined status of S. falconis and assumed that it might belong to a separate genus ( Cryptostrigea ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent use of an integrative approach combining morphology, molecular biology and the study of parasites and their hosts is essential and has made it possible to confirm or place species in synonymy and to understand the taxonomy within several genera of this family (Blasco-Costa et al 2016 ; Achatz et al 2020 ; Locke et al 2021 ; Pyrka et al 2021 ; Sokolov et al 2021 ). Regarding the genus Strigea , López-Jiménez et al ( 2023 ) analysed the South American species based on different nuclear and mitochondrial domains. Heneberg et al ( 2018 ) showed the separation of the European species into three clades ( Strigea sensu stricto, Amphistoma and Cryptostrigea ), proved the well-defined status of S. falconis and assumed that it might belong to a separate genus ( Cryptostrigea ).…”
Section: Discussionmentioning
confidence: 99%
“…The D2 domain of the rDNA (556 bp) and the partial ND1 (395 bp) and cox 1 (236 bp) domains of the mDNA were used for molecular comparisons and tree constructions. Phylogenetic trees were constructed based on previous analyses (Heneberg et al 2018 ; López-Jiménez et al 2023 ) and new taxa available in GenBank (Table 2 ), using the neighbour joining (NJ), the maximum likelihood (ML) and minimum evolution (ME) methods, using the MEGA version 11 software. Bayesian inference (BI) analysis was conducted using MrBayes v. 3.2.6 (Huelsenbeck and Ronquist 2001 ; Dereeper et al 2008 , 2010 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations